COMMUNITY ACCEPTABILITY TO THE SALAFI MOVEMENT - Setiawan, Wahyu; Midia, Fredy Gandhi (AKADEMIKA: Jurnal Pemikiran Islam, 2019)
The study of Salafi is generally focused on the perspective of social movements with the political opportunity structure, resources theory, and collective action frames. The three approaches to social movement theory lead to the same estuary, which is an analysis of emerging factors and the development of a social movement. Unlike the previous studies, this article focuses on the acceptance of the Islamic community's acceptability patterns to the Salafi movement. The interesting phenomenon of this movement is the so massive infiltration occurring. The community is so rapidly accepting the style and the system of sustainability offered by various Salafi groups. This article uses a sociological approach to the basis of structural-functional and interactionist-symbolic theories of experience in both the individual and collective levels of the followers of Salafi. Methods of collecting data through interviews, observations, and documentation with the research subject of 30 members of the Salafi group are not grass-root. The results showed that structuralist-functionally, the phenomenon of public acceptability due to the currents of modernity, shifting the concept of the family, shifting the meaning of religious authorities, and ease of access to information technology. Symbolically-symbolic, the phenomenon is the result of individual interaction with the social environment and the search for alternative religious identity. Keywords: Salafi, Movemnt, and Islam